Autophagy plays an important role in the containment of HIV-1 in nonprogressor-infected patients - Nardacci, Roberta (Landes Bioscience, 2014)
Recent in vitro studies have suggested that autophagy may play a role in both HIV-1 replication and disease progression. In this study we investigated whether autophagy protects the small proportion of HIV-1 infected individuals who remain clinically stable for years in the absence of antiretroviral therapy, these named long-term nonprogressors (LTNP) and elite controllers (EC). We found that peripheral blood mononuclear cells (PBMC) of the HIV-1 controllers present a significantly higher amount of autophagic vesicles associated with an increased expression of autophagic markers with respect to normal progressors. Of note, ex vivo treatment of PBMC from the HIV-1 controllers with the MTOR inhibitor rapamycin results in a more efficient autophagic response, leading to a reduced viral production. These data lead us to propose that autophagy contributes to limiting viral pathogenesis in HIV-1 controllers by targeting viral components for degradation.